2020
DOI: 10.21203/rs.2.22689/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Theory-lead Intervention for Knee Osteoarthritis in Older Adults: A Cluster Randomized Trial

Abstract: Background: Knee osteoarthritis (KOA) is a common joint disease in people over 60 years old. Exercise therapy is one of the most effective non-pharmacological treatments for KOA, but low exercise adherence needs to be improved. The present study aimed to evaluate the effect of the transtheoretical model-lead home exercise intervention (TTM-HEI) program on exercise adherence, KOA symptoms and knee function in older adults with KOA. Methods: A two-arm, superiority, assessor-blinded, cluster randomized trial was … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Among all kinds of rehabilitation therapy for arthritis, the role of exercise rehabilitation therapy is the most recognized by evidence-based medicine. Its functions promote blood circulation, enhance venous return and venous congestion, increase joint range of motion, muscle strength, and joint stability, promote the diffusion of synovial fluid to the cartilage surface and the intercellular substance, and can stimulate the proliferation of chondrocytes around the lesion area, supporting the regeneration of degenerated cartilage, and the strength of the sufferer's extensor muscles may increase the stability of the knee joint [ 12 ]. Clinical studies have shown that exercise rehabilitation is the most effective way to prevent and treat joint diseases and injuries and to support articular cartilage repair.…”
Section: Discussionmentioning
confidence: 99%
“…Among all kinds of rehabilitation therapy for arthritis, the role of exercise rehabilitation therapy is the most recognized by evidence-based medicine. Its functions promote blood circulation, enhance venous return and venous congestion, increase joint range of motion, muscle strength, and joint stability, promote the diffusion of synovial fluid to the cartilage surface and the intercellular substance, and can stimulate the proliferation of chondrocytes around the lesion area, supporting the regeneration of degenerated cartilage, and the strength of the sufferer's extensor muscles may increase the stability of the knee joint [ 12 ]. Clinical studies have shown that exercise rehabilitation is the most effective way to prevent and treat joint diseases and injuries and to support articular cartilage repair.…”
Section: Discussionmentioning
confidence: 99%
“…Pain can be studied or visualised by change in gait, licking, rubbing, abnormal posture or decreased food and water intake. 14,15…”
Section: Discussionmentioning
confidence: 99%